Personalized care of patients with heart failure: are we ready for a REWOLUTION? Insights from two international surveys on healthcare professionals' needs and patients' perceptions. (30th March 2023) - Jankowska, Ewa A.; Liu, Peter P.; Cowie, Martin R.; Groenhart, Max; Cobey, Kelly D.; Howlett, Jonathan; Komajda, Michel; Lund, Lars H.; Magaña Serrano, Jose Antonio; Mourilhe‐Rocha, Ricardo; Rosano, Giuseppe M.C.; Saldarriaga, Clara; et al.
Abstract: Aims: Guidelines for the management of heart failure (HF) are evolving, and increasing emphasis is placed on patient‐centred care. As part of the REWOLUTION HF (REal WOrLd EdUcaTION in HF) programme, we conducted two international surveys aimed at assessing healthcare professionals' (HCPs) educational needs and patients' perspectives on the care of HF. Methods and results: Anonymous online questionnaires co‐developed by HF experts and patients assessed HCPs' educational needs (520 respondents, mostly cardiologists, in 67 countries) and patients' perceptions on HF impact and management (98 respondents in 18 countries). Among HCPs, 62.7% prioritized rapid initiation of all guideline‐mandated medications over up‐titration of some medications, and 87.7% always or frequently discussed treatment goals with patients. There was good agreement between HCPs and patients on key treatment goals, except for a greater emphasis on reducing hospitalizations among HCPs. The most frequently cited barriers to the provision of guideline‐recommended pharmacological therapy were treatment side effects/intolerance, complex treatment regimens, low blood pressure, cost/reimbursement issues, and low estimated glomerular filtration rate. Most patients (81.6%) reported no difficulties taking medications as prescribed, although 21.4% felt they were taking too many pills. Patients wanted more information about HF and its consequences, prognosis, and treatments (70.4%, 74.5% and 76.6%, respectively). Cardiologists were the preferred source of information about HF, followed by general practitioners and HF nurses. Conclusions: These surveys provide valuable insights into HCPs' needs about personalized care for patients with HF, as well as patients' perceptions, expectations and preferences. These findings will be helpful to develop patient‐centred, needs‐driven quality improvement programmes. Abstract : Personalized care of patients with heart failure (HF) – are we ready for a REWOLUTION? Insights from two international surveys on healthcare professionals' (HCP) needs and patients' perceptions.